TRIPLE BOTTOM LINE REPORTING - El Ghazaly, Mahmoud T. A. (أكاديمية السادات للعلوم الإدارية - مركز البحوث والاستشارات والتطوير, 2005)
This paper outlines Environmental and Social Reporting development. It analyses the importance of the issue and explains the changing role of accountants towards it. The paper depends mainly on textbooks, previous published articles, and World Wide Web cites. It concluded that the accounting and auditing standards should be modified in-order to reflect the environmental and social costs.
Keywords: التنظيم الإداري -- شبكات المعلومات -- المواقع الإلكترونية